Competition between lithium and magnesium ions for the G-protein transducin in the guanosine 5'-diphosphate bound conformation - Srinivasan, Chandra (2004)
Li+ is the most effective drug used to treat bipolar disorder; however, its exact mechanism of action has yet to be elucidated. One hypothesis is that Li+ competes with Mg2+ for the Mg2+ binding sites on guanine-nucleotide binding proteins (G-proteins). Using 7Li T1 relaxation measurements and fluorescence spectroscopy with the Mg2+ fluorophore furaptra, we detected Li+/Mg2+ competition in three preparations: the purified G-protein transducin (Gt), stripped rod outer segment membranes (SROS), and SROS with purified Gt reattached (ROS-T). When purified ROS-T, SROS or transducin were titrated with Li+ in the presence of fixed amounts of Mg2+, the apparent Li+ binding constant decreased due to Li+/Mg2+ competition. Whereas for SROS the competition mechanism was monophasic, for Gt, the competition was biphasic, suggesting that in Gt, Li+/Mg2+ competition occurred with different affinities for Mg2+ in two types of Mg2+ binding sites. Moreover, as [Li+] increased, the fluorescence excitation spectra of both ROS-T and Gt were blue shifted, indicating an increase in free [Mg2+] compatible with Li+ displacement of Mg2+ from two low affinity Mg2+ binding sites of Gt. Gt release from ROS-T membrane was also inhibited by Li+ addition. In summary, we found evidence of Li+/Mg2+ competition in Gt-containing preparations.